Basic needs and employment, the crisis in the North and the South : the impact of the world recession on employment and poverty in developing countries (ILO GenevaCH, 1985)
Assesses impact of post 1979 recession on developing countries focusing on the social groups most affected. Discusses relationship of growth in OECD countries to that of developing countries highlighting need for policy changes in the latter. Discusses impact of recession on Latin American workers, on Sub-Saharan African countries, and on developing economies in Asia.
Includes bibliographical references